GUIDANCE TESTS FOR ACCOUNTING STUDENTS. - Littleton, A. C. (The Accounting Review, 1946)
A committee on selection of personnel was established by the American Institute of Accountants in 1943 in the U.S., to study ways and means of insuring a continuing influx of capable people into the profession of accounting. Obviously, vocational counseling would sooner or later be involved. If counseling could avoid some of the heartbreaking experiences often met in fumbling and stumbling into one's life work, it would surely be worth while to the individual, and no less to the profession. It is clear, too, that counseling could work best if it rested on factual evidence regarding the individual's capability and promise. To furnish some evidence of this kind, tests would be needed that would be revealing, that could be easily administered, and that might be so widely used as to furnish national norms as a standard of comparison. The purpose of the present project of the committee is to define the mental and personal qualities which make for success in professional accounting. It also aims to develop, in collaboration with educational institutions, a procedure whereby promising young men may be discovered and guided towards the profession establish a battery of tests and supplementary techniques.